Some Design Issues of Multi-Plate Magnetorheological Clutches (Hungarian Journal of Industry and Chemistry, 2011)
The most essential purpose of the modern society is that it’s able to handle and find solution for environmental problems especially water pollution which is serious problem not only for present but future generation as well. As the load to our surface water has become more significant consequently a continuously increasing demand has been created for adequate water quality and quantity water. The Water Framework Directive is a long-term water policy of the European Union. Aim of WFD is the classification and protection of the water according to consistent viewpoints. Objectives of the researches are the identification and testing of the effects of the potential pollutants sources and critical sites in Séd (Veszprém) and in Sebes-Körös in Békés.